A clinical guide to autistic spectrum disorders - Evans, Patricia, 1956-; Morris, Mary Ann. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"Sad to say, most medical school and residency programs fail to prepare physicians very well to recognize the less obvious forms of autism spectrum disorder or to appropriately manage children with autism. Clinical neuroscience training, at whatever level, tends to emphasize global failure of cognitive development or the subsequent loss of one or more cognitive functions due to structural lesions or diffuse degenerative processes. Neither of these models suit children with autism spectrum disorders very well. Inexperience in the management of autism has become particularly problematic because of the increased frequency of its diagnosis in recent years and the increased recognition of milder autism phenotypes"--Provided by publisher.
section one. Introduction to austistic spectrum disorders -- section two. Symptom-based assessment -- section three. Therapeutic approaches -- section four. Austism spectrum disorders and the public school.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Autism spectrum disorders; Autism in children; Autism spectrum disorders -- Treatment; Electronic books